2019
DOI: 10.1002/jcb.27908
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene coexpression modules, hub genes, and pathways related to spinal cord injury using integrated bioinformatics methods

Abstract: Spinal cord injury (SCI) is characterized by dramatic neurons loss and axonal regeneration suppression. The underlying mechanism associated with SCI‐induced immune suppression is still unclear. Weighted gene coexpression network analysis (WGCNA) is now widely applied for the identification of the coexpressed modules, hub genes, and pathways associated with clinic traits of diseases. We performed this study to identify hub genes associated with SCI development. Gene Expression Omnibus (GEO) data sets GSE45006 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…It has been used to study diseases which affect the neurological system, such as neuropathic pain (15), Parkinson's disease (16), and Alzheimer's disease (17). This method has also been successfully utilized in previous studies to identify pathway-related modules in SCI patients (18). Hence, the co-expression network for models and hubs of SCI genes is accessible; however, the number of studies addressing this issue remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to study diseases which affect the neurological system, such as neuropathic pain (15), Parkinson's disease (16), and Alzheimer's disease (17). This method has also been successfully utilized in previous studies to identify pathway-related modules in SCI patients (18). Hence, the co-expression network for models and hubs of SCI genes is accessible; however, the number of studies addressing this issue remains insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies on SCI applied WGCNA. For example, Wang et al used WGCNA in 2 open access array data and identified 3 hub genes including Rac2, Itgb2 and Tyrobp , which may play crucial roles in SCI via natural killer cell-mediated cytotoxicity [ 37 ]. Another study using WGCNA indicated that the effects of NT3-chitosan on neurite regeneration were mediated by the enhancement in neurogenesis and angiogenesis and reduced inflammatory responses [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cut height of 0.85 and effect size of ≥10 were used to identify the modules. Pearson's correlation matrices were calculated for the modules (20).…”
Section: Methodsmentioning
confidence: 99%